2019
DOI: 10.1038/s41598-018-37180-8
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Functionalization of gold-nanoparticles by the Clostridium perfringens enterotoxin C-terminus for tumor cell ablation using the gold nanoparticle-mediated laser perforation technique

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In the previous study, we showed that the energy power of the applied laser at 60 mJ/cm 3 and a scanning speed of 0.5 cm/s in combination with C-CPE-AuNPs reduced cell survival to less than 30% of claudin expressing cell lines [36]. In a rst experiment, GNOME-LP with the same settings accordingly reduced cell survival to about 30% in native DT0846 cells, but showed no effect on the transfected uorescence cells (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the previous study, we showed that the energy power of the applied laser at 60 mJ/cm 3 and a scanning speed of 0.5 cm/s in combination with C-CPE-AuNPs reduced cell survival to less than 30% of claudin expressing cell lines [36]. In a rst experiment, GNOME-LP with the same settings accordingly reduced cell survival to about 30% in native DT0846 cells, but showed no effect on the transfected uorescence cells (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…However, studies in vivo revealed that systemic administration of full-length CPE in mice was toxic and thus limited its use to local therapies [52]. Previously we demonstrated that the noncytotoxic C-terminal domain of CPE, which preserves CPE's binding a nity to CLDN receptors, is capable to functionalize AuNPs [36]. Imaging of C-CPE binding to the canine tumor cell lines proved that the protein can speci cally target CLDN3, -4 and − 7 demonstrating that the functionalization did not alter the binding capacity to CLDN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous published study demonstrated that the noncytotoxic C-terminal domain of CPE, which preserves CPE's binding affinity to CLDN receptors, is capable of functionalizing AuNPs. The imaging of C-CPE binding to the canine tumor cell lines proved that the protein can specifically target CLDN-3, -4, and -7, demonstrating that the functionalization did not alter the binding capacity to CLDN [43].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of our group confirmed that the C-CPE bound to cell lines expressing CLDN-3, -4, and -7 but was not able to target cells without CLDN-3, -4, and -7 expression. Furthermore, we demonstrated that C-CPE-AuNPs can be used to specifically and efficiently ablate different human cell lines expressing CLDN-3, -4, and -7 by gold-nanoparticle-mediated laser perforation (GNOME-LP) technique [43,44]. However, the used cell lines do not allow one to realize experimental in vivo experiments going for deep tissue imaging.…”
Section: Introductionmentioning
confidence: 99%